Recent advances on nanomaterial-modified film-electrode-based sensors: Approach to clinical purpose - Jampasa, Sakda; Khamcharoen, Wisarut; Traipop, Surinya; Jesadabundit, Whitchuta; Ozer, Tugba; Chailapakul, Orawon (ELSEVIER, 2023)
Nanomaterial-modified sensors are significant key factors for developing electrochemical devices, especially for clinical purposes. Incorporating nanomaterials on film-electrode based sensors possesses a wide range of effective deployments, such as screening, monitoring, and tracking various diseases. Many attempts have been made to develop thin-/thick-film-electrode-based sensors for this particular purpose, and it is explored that the sensors modified with nano materials exhibited enhanced properties. This review provides a concise description of nanomaterials, their types including polymers, metals, and carbon-based nanocomposites, and their importance for clinical sensing applications. The accountability of each nanomaterial used for presented electrochemical sensors is discussed. This novel overview further sheds light on the future perspectives of nanomaterial-modified-film sensors for their future directions to diverse clinical applications.
Keywords: Nanomaterials; Film-electrode-based sensor; Diagnostics; Electrochemical sensor; THIN-FILM; MEMBRANE; Chemistry; Electrochemistry; Materials Science